1997
DOI: 10.1212/wnl.49.4.1190
|View full text |Cite
|
Sign up to set email alerts
|

Red ear syndrome

Abstract: Red ear syndromeTo the Editor: As an addendum t o Dr. Lance's eloquent presentation of 12 cases of "red ear syndrome,"' I would add bilaterality and suggest the new name "red ears syndrome." Despite his case #8 (which was bilateral), Lance characterizes red ear syndrome as unilateral change in color with burning pain that may extend beyond the ear. In 1987 I studied 29 vascular or mixed vascular/ muscle contraction headache patients and 29 headache-free controls.2 Whereas 14 patients in the headache group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 3 publications
1
24
0
Order By: Relevance
“…He did not have any apparent predisposing factor or etiology as described above. 6,7,9 However, even though it could not be a complete explanation, thalamic lesion would be the most probable cause of red ear(s) syndrome in this patient because our patient showed the vasculitis of left middle cerebral artery and infarction in left basal ganglia, which might involve the thalamus.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…He did not have any apparent predisposing factor or etiology as described above. 6,7,9 However, even though it could not be a complete explanation, thalamic lesion would be the most probable cause of red ear(s) syndrome in this patient because our patient showed the vasculitis of left middle cerebral artery and infarction in left basal ganglia, which might involve the thalamus.…”
Section: Discussionmentioning
confidence: 68%
“…6 Hirsch reported the presence of red ear(s) syndrome in patients with headache, which may be caused by an underlying dysregulation of sympathetic out¯ow. 7 O'Gradaigh et al reported swollen tender indurated red ears and adjacent skin in antiphospholipid syndrome, which resulted from bilateral thrombosis of ears. 9 The etiology of red ears in our patient is obscure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The key clinical feature of RES is the presence of burning ear pain associated with marked ear reddening although Hirsch reported five patients with episodes of bright red discoloration of the ears not associated with auricular pain [18]. The erythema of the ear consistently follows the ear pain and usually lasts as long as the burning pain does.…”
Section: Reviewmentioning
confidence: 99%
“…Other secondary pathologies have been associated with the syndrome, including Chiari I malformation, congenital anomalies of the cervical spine [14], herpes zoster virus infection of the C3-C6 dermatomes, and exercise-induced compression of the cerebellar tonsils [3]. Furthermore, the disorder need not necessarily result in significant ear pain, but rather only redness of the ear [4].…”
Section: Introductionmentioning
confidence: 99%